Outcome of spinal decompression in traumatic cauda equina syndrome: An analysis of 4 cases in HTAA, Kuantan - Izhar, Mohammad Izzad; Mahfoodz, Ahmad Hud; Mor Japar Khan, Ed Simor Khan (2018)
INTRODUCTION: The objective of this study is to analyze the outcome of surgery in spinal decompression in patient who was diagnosed as traumatic cauda equina syndorme (CES) in relation to time to surgery as variable to determine its association with outcomes in CES. MATERIALS & METHODS: This is a retrospective study. All patients was selected at a single center whose medical record allowed precise calculation of time to surgery were included. CES was defined as perineal anesthesia and other lumbosacral root sensory deficits, lower extremity weakness, difficulty with bladder and bowel control, sexual dysfunction, low back pain, and unilateral or bilateral sciatica. CES can be divided into two types, complete or incomplete. Complete CES presented with saddle anesthesia and bladder or bowel retention/incontinence, while incomplete CES patients presented with saddle anesthesia but with minor bladder and bowel dysfunction such as loss of urgency or altered urinary sensorium. Outcome of surgery was analyzed with relation to time of surgery starting when the diagnosis of traumatic CES is made as a variable. RESULTS: Four patients were identified by using their medical record from spine clinic. Analysis of time showed significant association with outcomes. Age, sex, and race, acute onset of CES, saddle anesthesia, motor deficit, and bowel dysfunction at presentation was used to analyze the continuous influence of time to surgery on bladder dysfunction and an aggregate outcome of symptoms. The timing of surgery more than 72 hours were significantly associated with persistent CES outcome post operatively. Also noted, the delay of diagnosis is due to incomplete neurological assessment in patients due to insertion of urinary Foley catheters in all trauma patients. Post operatively, continuous monitoring for at least six months revealed all patients still not recovered from CES. DISCUSSIONS: Acute trauma as a cause of cauda equina syndrome is very rare. All patients had no associated visible lesions and this indicates that this problem can be seen with a much milder clinical picture (i.e. fall from coconut tree/building). Three of the selected patients was referred from district hospital and was already late in establishing diagnosis of CES upon arriving to emergency unit in HTAA. Cauda equina syndrome is an uncommon entity following spinal column trauma. Most of the reported literature supports early intervention for return of full neurologic function for cauda equina syndrome but there is no consensus on the optimal time of decompression. Early intervention (less than 72 hours) is required for favorable return of neurological functions. Even in case of late referrals, the orthopedic surgeon should not hesitate to do the necessary operation including the decompression of the neural elements and stabilization of the spine. If spinal decompression is done properly, and segmental